TI_GERICHTE 14.2011.214 vom 11. Januar 2012 , Reclamo contro la dichiarazione di fallimento. Legittimazione a ricorrere - TI Tribunale d'appello (2012)
Reclamo contro la dichiarazione di fallimento. Legittimazione a ricorrere